Functional membrane for recovering precious metals in wastewater and preparation method thereof

By using a polyamide fiber web combined with functional modifications of carboxymethyl chitosan, hollow mesoporous nanosilia and epoxy silane coupling agent, a functional film for efficient recycling of precious metals in wastewater was constructed, solving the problems of high cost, low efficiency and structural instability in the prior art, and achieving efficient recycling effects suitable for industrial production.

CN119633622AActive Publication Date: 2025-03-18JIANGXI PUHE SHENGYE ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202510090150.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art has problems of high cost, low efficiency and unstable structure when recycling precious metals in wastewater, making it difficult to be applicable to industrial scale production.

Method used

Polyamide is used as a film-forming substance to form a polyamide fiber web through electrospinning process, and on its surface, it is cross-linked by carboxymethyl chitosan and hollow mesoporous nanosilia, combined with functional modification of epoxy silane coupling agent and adipic acid dihydrazide, to construct a functional film that efficiently recovers precious metal ions.

Benefits of technology

It realizes efficient recycling of precious metals in wastewater, reduces production costs, improves the mechanical properties and structural stability of the membrane, and is suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633622A_ABST
    Figure CN119633622A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater resourceful treatment, in particular to a functional membrane for recycling precious metals in wastewater and a preparation method of the functional membrane. The specific preparation method comprises the following steps: preparing a polyamide spinning solution, carrying out electrostatic spinning on the spinning solution to form a polyamide fiber net, stably combining hollow mesoporous nano silicon dioxide on the fiber net through carboxymethyl chitosan, and grafting an epoxy silane coupling agent on the surface of the hollow mesoporous nano silicon dioxide to obtain the hollow mesoporous nano silicon dioxide fiber net. Finally, adipic dihydrazide is grafted on the hollow mesoporous nano silicon dioxide through a ring-opening reaction. Organic polyamide is used as a film forming substance, the raw material cost is low, the method is suitable for large-scale industrial production, the recovery rate of precious metal ions is high, and the film body has good mechanical strength and can stably operate for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater resource treatment, and in particular to a functional membrane for recovering precious metals in wastewater and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, precious metals have been widely used in many fields such as electronics, chemical industry, and medicine. However, a large amount of wastewater containing precious metals will be generated in these industrial production processes. If it is discharged directly, it will not only cause serious environmental pollution, but also lead to a huge waste of precious metal resources. Traditional wastewater treatment methods, such as chemical precipitation and ion exchange, can remove precious metals in wastewater to a certain extent, but they have many limitations. Chemical precipitation may produce a large amount of chemical sludge, which has high subsequent treatment costs and is prone to secondary pollution; the resin regeneration process of ion exchange is relatively complicated and has limited effect on high-concentration wastewater treatment. In recent years, membrane technology has shown great application potential in the field of wastewater treatment due to its advantages such as high efficiency, energy saving, and simple operation. Membrane recovery technology can achieve efficient separation and recovery of precious metals in wastewater by selecting suitable membrane materials and operating conditions, while reducing the impact on the environment, and has significant economic and environmental benefits.

[0003] Chinese patent publication number CN117623445A discloses a functional membrane for recovering precious metal ions from oily wastewater and a preparation method thereof, the method comprising the following steps: preparing carbon nanotubes CNTs-PAH modified with hydrazide functional groups; firstly grafting acrylic acid onto the surface of carbon nanotubes by grafting polymerization to obtain the first step product CNTs-PAA, and then using adipic acid dihydrazide to react with carboxyl functional groups to obtain carbon nanotubes (CNTs-PAH) modified with hydrazide functional groups; preparing a single-layer MXene nanosheet; and preparing CNTs-PAH / MXene composite membranes based on CNTs-PAH and MXene by vacuum filtration. This technical solution uses carbon nanotubes and MXene nanosheets as film-forming materials, and the raw material cost is relatively high, which is not suitable for industrial-scale production. Summary of the invention

[0004] In order to overcome the above problems of the prior art, the present invention provides a functional membrane for recovering precious metals in wastewater and a preparation method thereof. The present invention uses organic polyamide as a membrane-forming material, has low raw material cost, is suitable for large-scale industrial production, has a high recovery rate for precious metal ions, and the membrane itself has good mechanical strength and can operate stably for a long time.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0007] 1) adding polyamide into a solvent to prepare a spinning solution, and electrospinning the spinning solution into a polyamide fiber web for later use;

[0008] 2) adding carboxymethyl chitosan into a solvent to prepare a carboxymethyl chitosan solution, adding the hollow mesoporous nano-silica into the carboxymethyl chitosan solution, dispersing the hollow mesoporous nano-silica uniformly, and obtaining a mixed solution;

[0009] 3) immersing the polyamide fiber web in the mixed solution, adding a crosslinking agent, and performing a crosslinking reaction to obtain a polyamide fiber membrane;

[0010] 4) adding an epoxy silane coupling agent to a solvent, stirring and hydrolyzing to obtain a hydrolyzate, immersing the polyamide fiber membrane in the hydrolyzate, heating and reacting, and obtaining an epoxy silane coupling agent grafted modified polyamide fiber membrane;

[0011] 5) Add adipic acid dihydrazide to a solvent to prepare an adipic acid dihydrazide solution, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution, heat to react, take out and dry to obtain the membrane.

[0012] The functional membrane for recovering precious metals in wastewater of the present invention uses polyamide as a membrane-forming material, which has the advantage of low price compared to the membrane-forming materials in the prior art and can be suitable for large-scale industrial production. The functional membrane of the present invention uses polyamide as a membrane-forming material, forms a polyamide fiber mesh through an electrostatic spinning process, and constructs a stable membrane infrastructure with a high specific surface area. Carboxymethyl chitosan is cross-linked on the polyamide fiber mesh to firmly bind the hollow mesoporous nano-silica to the surface of the fiber mesh, providing a good platform for subsequent functional modification. Through the dehydration reaction of the epoxy silane coupling agent and the hydroxyl group on the surface of the hollow mesoporous nano-silica, the epoxy silane coupling agent is successfully grafted, so that the hollow mesoporous nano-silica is loaded with epoxy functional groups, and then the ring-opening reaction of the epoxy functional group and the amino group on the adipic acid dihydrazide is used to graft the adipic acid dihydrazide on the surface of the nano-silica, forming a set of orderly and efficient functional construction processes.

[0013] The functional groups on adipic acid dihydrazide have a strong complexing ability for the precious metal ions in the wastewater, and can react specifically with the precious metal ions to achieve accurate capture of the precious metal ions. At the same time, the hollow mesoporous nano-silica plays a dual role. On the one hand, as a carrier, it efficiently loads the grafted adipic acid dihydrazide and increases the active sites for reaction with the precious metal ions; on the other hand, its unique hollow mesoporous structure greatly enhances the adsorption capacity for the precious metals in the wastewater, and can adsorb a large amount of precious metal ions from the wastewater. The synergistic effect of these two aspects enables the functional membrane of the present invention to show a very high recovery rate and recovery efficiency when recovering the precious metal ions in the wastewater, and can achieve deep purification and recycling of the precious metals in the wastewater, effectively reducing the cost of wastewater treatment and improving the recycling rate of resources.

[0014] Preferably, in step 1), the mass concentration of polyamide in the spinning solution is 15-20%.

[0015] Preferably, hexadecyltrimethylammonium bromide is also added to the spinning solution in step 1).

[0016] In the technical solution of the present invention, as described above, the hollow nano-silica is fixed on the polyamide fiber net through the cross-linking reaction of carboxymethyl chitosan, but there is a further problem that carboxymethyl chitosan and hollow mesoporous nano-silica are difficult to be well combined on the surface of the polyamide fiber net and undergo a cross-linking reaction. This problem affects the structural integrity and performance stability of the functional membrane, and limits its recovery effect on precious metals in wastewater. In view of the above problems, the present invention innovatively adds hexadecyl trimethyl ammonium bromide to the polyamide spinning solution. Hexadecyl trimethyl ammonium bromide is a cationic surfactant, and its molecules are positively charged. In contrast, the surfaces of hollow mesoporous nano-silica and carboxymethyl chitosan are both negatively charged. After hexadecyl trimethyl ammonium bromide is added to the polyamide spinning solution, in the subsequent preparation process, due to the effect of electrostatic attraction, the positively charged hexadecyl trimethyl ammonium bromide can attract each other with the negatively charged hollow mesoporous nano-silica and carboxymethyl chitosan. This electrostatic attraction acts like a bridge, tightly connecting the hollow mesoporous nano-silica and carboxymethyl chitosan to the surface of the polyamide fiber mesh. Under the action of the cross-linking agent, carboxymethyl chitosan can more efficiently undergo self-cross-linking reaction on the surface of the polyamide fiber mesh. At the same time, the hollow mesoporous nano-silica can also be more firmly fixed on the surface of the polyamide fiber mesh with the help of this electrostatic attraction and cross-linking reaction, forming a more stable and compact structure. Compared with the original scheme, by introducing electrostatic attraction, the hollow nano-silica is better bonded to the polyamide fiber mesh, and the bonding stability of carboxymethyl chitosan and hollow mesoporous nano-silica on the surface of the polyamide fiber mesh is significantly improved. This makes the functional membrane have a better recovery effect on precious metal ions in actual application, and can withstand greater water flow impact and chemical environment changes. It is not easy for functional materials to fall off, which effectively extends the service life of the functional membrane.

[0017] In addition, the self-crosslinking reaction of carboxymethyl chitosan on the surface of the polyamide fiber mesh is promoted by the action of electrostatic attraction, making the crosslinking process more complete and uniform. This not only helps to improve the mechanical strength of the functional membrane, but also optimizes the microstructure of the membrane, making its adsorption and complexation site distribution of precious metal ions in wastewater more reasonable, thereby improving the recovery capacity and efficiency of precious metal ions. The stably combined and fully cross-linked hollow mesoporous nano-silica and carboxymethyl chitosan can better play their respective functional advantages. The adsorption performance of hollow mesoporous nano-silica and the complexation performance brought about by the subsequent reaction of carboxymethyl chitosan and adipic acid dihydrazide are fully guaranteed, thereby achieving more efficient and accurate recovery of precious metal ions in wastewater, further improving the application value of the entire functional membrane in the field of wastewater treatment.

[0018] Preferably, the mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 3.0-5.0%.

[0019] In the technical solution of the present invention, the mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is precisely controlled, which brings significant and diverse technical effects. When the mass concentration of hexadecyltrimethylammonium bromide is lower than 3%, the charge of the polyamide fiber mesh is too low, and it is difficult to build a strong electrostatic attraction with the hollow monitoring nano-silica and carboxymethyl chitosan. The lower limit of the concentration of the present invention is set to ensure the effective combination of the components, ensure that the electrostatic attraction effect in the system is fully exerted, and make the composite effect of the functional material reach the best state. Therefore, the present invention controls the mass concentration of hexadecyltrimethylammonium bromide to be higher than 3%.

[0020] However, another problem encountered by the team of the present invention during the research and development process is that the water pressure resistance of some functional membranes prepared has dropped significantly. After research by the team of the present invention, it was found that this problem is related to the mass concentration of hexadecyltrimethylammonium bromide. When the mass concentration of hexadecyltrimethylammonium bromide exceeds a certain amount, the distribution of hexadecyltrimethylammonium bromide molecules in the polyamide fiber membrane is too dense, and its presence may interfere with the original hydrogen bonds and other interactions between the polyamide molecular chains. The hydrogen bonds between the polyamide molecular chains play an important role in maintaining the mechanical strength of the fiber membrane. Excessive hexadecyltrimethylammonium bromide molecules may weaken this hydrogen bonding effect, resulting in a decrease in the binding force between the molecular chains, thereby reducing the mechanical strength, and then reducing its compressive strength. Therefore, the present invention simultaneously controls the mass concentration of hexadecyltrimethylammonium bromide to be less than 5%, maintains the water pressure resistance of the polyamide membrane, ensures that the prepared functional membrane maintains stable and reliable performance when facing a complex use environment, prolongs the actual service life of the functional membrane, and enhances the practicality and applicability of the product.

[0021] Preferably, in step 2), the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.1-0.7.

[0022] Preferably, in step 3), the amount of cross-linking agent added is 0.5-2.0% of the mass of the mixed solution.

[0023] Preferably, in step 4), the epoxysilane coupling agent is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0024] Preferably, in step 4), the heating reaction temperature is 50-60°C and the heating reaction time is 3-5h. Preferably, in step 5), the heating reaction temperature is 80-90°C and the heating reaction time is 4-9h. A functional membrane for recovering precious metals in wastewater is prepared by the above method.

[0025] The present invention has the following beneficial effects:

[0026] 1) Using polyamide with relatively low raw material cost as the film-forming material significantly reduces the production cost compared with the prior art using carbon nanotubes as the film-forming material, and is suitable for industrial production;

[0027] 2) The precious metal recovery functional membrane has a good complex recovery effect on precious metals and precious metal ions, and the membrane itself has stable structural performance and good mechanical properties.

[0028] Instruction Manual

[0029] Figure 1 This is an electron scanning microscope image of the surface of the functional membrane for recovering precious metals in wastewater prepared by the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0031] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0032] Example 1

[0033] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0034] 1) adding polyamide 6 to formic acid (analytical grade) to prepare a spinning solution with a mass concentration of 19%, then adding hexadecyltrimethylammonium bromide, wherein the mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 4.5%, stirring and mixing evenly, and electrospinning the spinning solution into a polyamide fiber mesh by electrostatic spinning, wherein the electrostatic spinning voltage is set to 20 kV; 2) adding carboxymethyl chitosan to its ionized water to prepare a carboxymethyl chitosan solution with a mass concentration of 1.5%, adding hollow mesoporous nano-silica to the carboxymethyl chitosan solution, wherein the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.6, and dispersing evenly by ultrasonic oscillation to obtain a mixed solution;

[0035] 3) immersing the polyamide fiber mesh in the mixed solution at a bath ratio of 1:20, adding glutaraldehyde in an amount of 1.5% of the mass of the mixed solution, heating to 50° C., and cross-linking reaction for 5 hours to obtain a polyamide fiber membrane;

[0036] 4) adding γ-glycidyloxypropyltrimethoxysilane to a solvent at a mass volume ratio of 1 g / 30 mL, wherein the solvent is a mixture of ethanol and water at a volume ratio of 10:1, stirring and hydrolyzing to obtain a hydrolyzate, immersing a polyamide fiber membrane in the hydrolyzate at a bath ratio of 1:20, reacting at a temperature of 60° C. for 3 hours, and obtaining a polyamide fiber membrane grafted with an epoxy silane coupling agent;

[0037] 5) Add adipic acid dihydrazide into deionized water, stir and dissolve to prepare a 3% adipic acid dihydrazide solution, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution at a bath ratio of 1:20, react at 90° C. for 4 hours, take out and dry to obtain the membrane.

[0038] Example 2

[0039] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0040] 1) adding polyamide 6 to formic acid (analytical grade) to prepare a spinning solution with a mass concentration of 16%, then adding hexadecyltrimethylammonium bromide, wherein the mass concentration of the hexadecyltrimethylammonium bromide in the spinning solution is 3.5%, stirring and mixing evenly, and electrospinning the spinning solution into a polyamide fiber web, wherein the electrospinning voltage is set to 20 kV; 2) adding carboxymethyl chitosan to its ionized water to prepare a carboxymethyl chitosan solution with a mass concentration of 1.5%, adding hollow mesoporous nano-silica to the carboxymethyl chitosan solution, wherein the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.2, and dispersing evenly by ultrasonic oscillation to obtain a mixed solution;

[0041] 3) immersing the polyamide fiber mesh in the mixed solution at a bath ratio of 1:20, adding glutaraldehyde in an amount of 0.8% of the mass of the mixed solution, heating to 50° C., and performing a cross-linking reaction for 5 hours to obtain a polyamide fiber membrane;

[0042] 4) adding γ-glycidyloxypropyltrimethoxysilane to a solvent at a mass volume ratio of 1 g / 30 mL, wherein the solvent is a mixture of ethanol and water at a volume ratio of 10:1, stirring and hydrolyzing to obtain a hydrolyzate, immersing a polyamide fiber membrane in the hydrolyzate at a bath ratio of 1:20, reacting at a temperature of 50° C. for 5 hours, and obtaining an epoxy silane coupling agent grafted modified polyamide fiber membrane;

[0043] 5) Add adipic acid dihydrazide into deionized water, stir and dissolve, prepare an adipic acid dihydrazide solution with a mass concentration of 3%, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution at a bath ratio of 1:20, react at a temperature of 80° C. for 9 hours, take out and dry to obtain the membrane.

[0044] Example 3

[0045] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0046] 1) adding polyamide 6 to formic acid (analytical grade) to prepare a spinning solution with a mass concentration of 17%, then adding hexadecyltrimethylammonium bromide, wherein the mass concentration of the hexadecyltrimethylammonium bromide in the spinning solution is 4.0%, stirring and mixing evenly, and electrospinning the spinning solution into a polyamide fiber mesh by electrostatic spinning, wherein the electrospinning voltage is set to 20 kV; 2) adding carboxymethyl chitosan to its ionized water to prepare a carboxymethyl chitosan solution with a mass concentration of 1.5%, adding hollow mesoporous nano-silica to the carboxymethyl chitosan solution, wherein the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.5, and dispersing evenly by ultrasonic oscillation to obtain a mixed solution;

[0047] 3) immersing the polyamide fiber mesh in the mixed solution at a bath ratio of 1:20, adding glutaraldehyde in an amount of 1.0% of the mass of the mixed solution, heating to 50° C., and performing a cross-linking reaction for 5 hours to obtain a polyamide fiber membrane;

[0048] 4) adding γ-glycidyloxypropyltrimethoxysilane to a solvent at a mass volume ratio of 1 g / 30 mL, wherein the solvent is a mixture of ethanol and water at a volume ratio of 10:1, stirring and hydrolyzing to obtain a hydrolyzate, immersing a polyamide fiber membrane in the hydrolyzate at a bath ratio of 1:20, reacting at a temperature of 60° C. for 3 hours, and obtaining a polyamide fiber membrane grafted with an epoxy silane coupling agent;

[0049] 5) Add adipic acid dihydrazide into deionized water, stir and dissolve to prepare a 3% adipic acid dihydrazide solution, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution at a bath ratio of 1:20, react at 90° C. for 4 hours, take out and dry to obtain the membrane.

[0050] Example 4

[0051] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0052] 1) adding polyamide 6 to formic acid (analytical grade) to prepare a spinning solution with a mass concentration of 20%, then adding hexadecyltrimethylammonium bromide, the mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 5.0%, stirring and mixing evenly, and electrospinning the spinning solution into a polyamide fiber mesh by electrostatic spinning, and the electrostatic spinning voltage is set to 20kV; 2) adding carboxymethyl chitosan to its ionized water to prepare a carboxymethyl chitosan solution with a mass concentration of 1.5%, adding hollow mesoporous nano-silica to the carboxymethyl chitosan solution, the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.7, and ultrasonic oscillation is used to disperse evenly to obtain a mixed solution;

[0053] 3) immersing the polyamide fiber mesh in the mixed solution at a bath ratio of 1:20, adding glutaraldehyde in an amount of 2.0% of the mass of the mixed solution, heating to 50° C., and performing a cross-linking reaction for 5 hours to obtain a polyamide fiber membrane;

[0054] 4) adding γ-glycidyloxypropyltrimethoxysilane to a solvent at a mass volume ratio of 1 g / 30 mL, wherein the solvent is a mixture of ethanol and water at a volume ratio of 10:1, stirring and hydrolyzing to obtain a hydrolyzate, immersing a polyamide fiber membrane in the hydrolyzate at a bath ratio of 1:20, reacting at a temperature of 50° C. for 5 hours, and obtaining an epoxy silane coupling agent grafted modified polyamide fiber membrane;

[0055] 5) Add adipic acid dihydrazide into deionized water, stir and dissolve, prepare an adipic acid dihydrazide solution with a mass concentration of 3%, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution at a bath ratio of 1:20, react at a temperature of 80° C. for 9 hours, take out and dry to obtain the membrane.

[0056] Example 5

[0057] A method for preparing a functional membrane for recovering precious metals in wastewater comprises the following steps:

[0058] 1) adding polyamide 6 to formic acid (analytical grade) to prepare a spinning solution with a mass concentration of 15%, then adding hexadecyltrimethylammonium bromide, wherein the mass concentration of the hexadecyltrimethylammonium bromide in the spinning solution is 3.0%, stirring and mixing evenly, and electrospinning the spinning solution into a polyamide fiber mesh by electrostatic spinning, wherein the electrostatic spinning voltage is set to 20 kV; 2) adding carboxymethyl chitosan to its ionized water to prepare a carboxymethyl chitosan solution with a mass concentration of 1.5%, adding hollow mesoporous nano-silica to the carboxymethyl chitosan solution, wherein the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.1, and dispersing evenly by ultrasonic oscillation to obtain a mixed solution;

[0059] 3) immersing the polyamide fiber mesh in the mixed solution according to a bath ratio of 1:20, adding glutaraldehyde in an amount of 0.5% of the mass of the mixed solution, heating to 50° C., and cross-linking reaction for 5 hours to obtain a polyamide fiber membrane;

[0060] 4) adding γ-glycidyloxypropyltrimethoxysilane to a solvent at a mass volume ratio of 1 g / 30 mL, wherein the solvent is a mixture of ethanol and water at a volume ratio of 10:1, stirring and hydrolyzing to obtain a hydrolyzate, immersing a polyamide fiber membrane in the hydrolyzate at a bath ratio of 1:20, reacting at a temperature of 60° C. for 3 hours, and obtaining a polyamide fiber membrane grafted with an epoxy silane coupling agent;

[0061] 5) Add adipic acid dihydrazide into deionized water, stir and dissolve to prepare a 3% adipic acid dihydrazide solution, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution at a bath ratio of 1:20, react at 90° C. for 4 hours, take out and dry to obtain the membrane.

[0062] Comparative Example 1

[0063] The difference between Comparative Example 1 and Example 1 is that:

[0064] Replace hollow nano-silica with ordinary nano-silica;

[0065] The remaining steps are the same as those in Example 1.

[0066] Comparative Example 2

[0067] The difference between Comparative Example 2 and Example 1 is:

[0068] In step 1), no hexadecyltrimethylammonium bromide is added to the spinning solution;

[0069] The remaining steps are the same as those in Example 1.

[0070] Comparative Example 3

[0071] The difference between Comparative Example 3 and Example 5 is that:

[0072] The mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 2.5%;

[0073] The remaining steps are the same as those in Example 5.

[0074] Comparative Example 4

[0075] The difference between Comparative Example 4 and Example 4 is that:

[0076] The mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 5.5%;

[0077] The remaining steps are the same as those in Example 4.

[0078] Comparative Example 5

[0079] The difference between Comparative Example 5 and Example 4 is that:

[0080] The mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 6.0%;

[0081] The remaining steps are the same as those in Example 4.

[0082] Performance Testing

[0083] 1. Test of precious metal recovery rate: HAuCl4 solution was used to simulate precious metal wastewater. The concentration of HAuCl4 solution was 60 mg / L. The precious metal recovery functional membrane was installed in the membrane evaluation device. The effective area of ​​the membrane was 12 cm 2 , at an operating pressure of 1 bar and a temperature of 25°C, the filtration was stably run for 1 hour, the filtrate was collected, the HAuCl4 concentration in the filtrate was tested after the filtration treatment, and the recovery rate of the precious metal was calculated by the following formula: R = (C0-C1) / C0×100%;

[0084] Wherein, C1 is the concentration of precious metal ions in the filtrate, and C0 is the concentration of precious metal ions in the original solution.

[0085] 2. Mechanical properties test: Use a cutter to cut 5 dumbbell-shaped specimens from the functional film. The length of the working part is 25mm and the width is 4mm. Use a vernier caliper to measure the width and thickness at three locations in the middle and on both sides of the working part of the specimen, and take the average value as the width and thickness data of the specimen. The measurement accuracy is accurate to 0.02mm, and the data is recorded. Place the cut specimens in a constant temperature and humidity chamber and place them for 48 hours at a temperature of 23±2℃ and a relative humidity of 50±5%RH to allow the specimens to reach a hygroscopic equilibrium state. According to the instrument operation manual, calibrate the universal material testing machine to ensure the measurement accuracy of the force sensor and displacement sensor, set the stretching speed to 10mm / min, select the appropriate load range, and ensure that the force value when the specimen breaks is within the range of 20%-80% of the range. Carefully clamp the specimen in the upper and lower clamps of the universal material testing machine to ensure that the center line of the specimen coincides with the center line of the clamp to avoid eccentric stretching. The clamping force is moderate to prevent the specimen from slipping or being clamped off during the stretching process. Start the universal material testing machine and start stretching the sample. Observe the stretching process of the sample and record the maximum force (F) when the sample breaks in N. Repeat the test 3 times for each sample and take the average value as the breaking force of the sample. Calculate the tensile strength of the film according to the following formula: t = F / A0;

[0086] Wherein, F is the maximum force when the specimen breaks, and A0 = average width of the specimen × average thickness.

[0087] Table 1:

[0088]

[0089] From the above test data, it can be seen that the functional membrane prepared in the embodiment has a higher recovery rate for precious metal ions, the recovery rate is more than 96%, while the recovery rate of the functional membranes of comparative examples 1-3 for precious metal ions is significantly lower than that of the embodiment.

[0090] The reason why the recovery rate of precious metal ions of the functional membrane of Comparative Example 1 is lower than that of the embodiment is that ordinary nano-silicon dioxide has no adsorption effect on precious metal ions, thereby affecting the complexation of adipic acid dihydrazide with precious metal ions. The reason why the recovery rate of precious metal ions of the functional membrane of Comparative Example 2 is lower than that of the embodiment is that hexadecyltrimethylammonium bromide is not added in Comparative Example 2, the membrane is not positively charged, and lacks the attraction to carboxymethyl cellulose and hollow mesoporous silica, resulting in relatively less hollow mesoporous silica being bound to the polyamide fiber membrane, thereby resulting in insufficient adipic acid dihydrazide loaded on the polyamide fiber membrane for complexation with precious metal ions.

[0091] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a functional membrane for recovering precious metals in wastewater, characterized in that: The following steps are involved: 1) adding polyamide into a solvent to prepare a spinning solution, and electrospinning the spinning solution into a polyamide fiber web for later use; 2) adding carboxymethyl chitosan into a solvent to prepare a carboxymethyl chitosan solution, adding the hollow mesoporous nano-silica into the carboxymethyl chitosan solution, dispersing the hollow mesoporous nano-silica uniformly, and obtaining a mixed solution; 3) immersing the polyamide fiber web in the mixed solution, adding a crosslinking agent, and performing a crosslinking reaction to obtain a polyamide fiber membrane; 4) adding an epoxy silane coupling agent to a solvent, stirring and hydrolyzing to obtain a hydrolyzate, immersing the polyamide fiber membrane in the hydrolyzate, heating and reacting, and obtaining an epoxy silane coupling agent grafted modified polyamide fiber membrane; 5) Add adipic acid dihydrazide to a solvent to prepare an adipic acid dihydrazide solution, immerse the epoxysilane coupling agent grafted modified polyamide fiber membrane in the adipic acid dihydrazide solution, heat to react, take out and dry to obtain the membrane.

2. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 1), the mass concentration of polyamide in the spinning solution is 15-20%.

3. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 1), hexadecyltrimethylammonium bromide is also added to the spinning solution.

4. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 3, characterized in that: The mass concentration of hexadecyltrimethylammonium bromide in the spinning solution is 3.0-5.0%.

5. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 2), the mass ratio of carboxymethyl chitosan to hollow mesoporous nano-silica is 2:0.1-0.

7.

6. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 3), the amount of cross-linking agent added is 0.5-2.0% of the mass of the mixed solution.

7. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 4), the epoxysilane coupling agent is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

8. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 4), the heating reaction temperature is 50-60° C. and the heating reaction time is 3-5 h.

9. The method for preparing a functional membrane for recovering precious metals in wastewater according to claim 1, characterized in that: In the step 5), the heating reaction temperature is 80-90° C. and the heating reaction time is 4-9 hours.

10. A functional membrane for recovering precious metals from wastewater, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and application of functional membrane for recovering noble metal ions from oily wastewater

    CN117623445A

  • Applications of mesoporous silica nano-sheet composite film in water treatment

    CN110743379A

  • High-flux antibacterial reverse osmosis membrane as well as preparation method and application thereof

    CN114917776A

  • Recycling method of precious metal

    CN119220824A

  • Separation function layer and separation membrane

    WO2024166604A1

Cited By

  • Preparation method of fiber polyamide forward osmosis membrane

    CN120094429A

  • A method for preparing a fiber polyamide forward osmosis membrane

    CN120094429B

  • Method for recovering precious metal from refining wastewater

    CN121135038A

  • Dual-functional chitosan / nano silicon dioxide composite aerogel as well as method and application thereof

    CN122141561A